Viability of Pony Stallion Semen in Different Temperature and Dilution - Trentin, Janislene Mach; Rodrigues, Murilo Farias; Pessoa, Gilson Antonio; Fiorenza, Mariani Farias; Schenatto, Ricardo Olimpio; Araujo, Laurence Boligon de; Aires, Karine Vargas; Rubin, Mara Iolanda Batistella (Acta Scientiae Veterinariae, 2017)
Background: Artificial insemination and transport of cooled semen has been routinely used in equine industry in the past 20 years. However, more investigations are needed regarding the methods for long time storage in pony stallion semen. The effect of dilution and cooling temperature on pH, sperm motility, membrane integrity and mitochondrial activity were investigated before and after cooling of stallion semen. Materials, Methods & Results: Two ejaculates each from nine Brazilian ponies were diluted in a nonbuffered powder milk extender cooled at 5°C or 15°C for 48 h using three different dilutions (1:1, 1:2 or 1:3). Data were assessed by analysis of variance and the rate comparison was performed using the Duncan test. Samples diluted 1:1 at 5oC or 15°C showed higher pH values (7.63 ± 0.34 e 7.57 ± 0.27) and lower progressive motility (10.3 ± 11.05, 17.08 ± 9.95). All samples cooled at 15°C also showed lower incidence of morphologically altered spermatozoa (1:1 = 55.84%; 1:2 = 51.84%; 1:3 = 49.95%) [P < 0.01]. Mitochondrial activity was higher on the 1:3 dilution (0.86 ± 0.19 nm) at 5°C and on the 1:1 (0.89 ± 0.23 nm), 1:2 (0.93 ± 0.2 nm) and 1:3 (0.92 ± 0.2 nm) dilutions at 15°C. Progressive motility was higher when semen was diluted 1:3 and cooled at 15°C (42.22 ± 12.38; P < 0.05). Considering mitochondrial activity, similar results were observed when different dilutions of semen were used (P > 0.05) despite time and temperature. The pH, progressive motility, mitochondrial activity and membrane integrity remained similar (P > 0.05) on fresh semen samples independent of the dilution grade used. The best results were obtained when semen was diluted 1:3 and cooled at 15°C. All dilution grades were safe for fresh semen and pH wasincreased when semen was diluted and cooled for 48 h. Discussion: The methodology used to collect and process equine semen and semen from ponies is practically the same. Equine semen when sent for artificial insemination is usually cooled to 5°C. Our results showed that cooling reduces sperm viability, which has also been demonstrated by other studies. In contrast, the best cooling temperature was at 15°C. However, it is easier to keep the temperature at 5°C during transport, due to the large temperature oscillation that may occur during transportation. The semen of ponies can tolerate cooling at both 5 and 15°C. The 1:3 dilution cooled to 15°C provided better viability of pony sperm, and more stable pH during 48 h of cooling. Dilution 1:1 should not be used for cooling in powdered skim milk extender.